2012
DOI: 10.1117/1.jbo.17.12.125005
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser ablation of bovine cortical bone

Abstract: We study the surface topographical, structural, and compositional modifications induced in bovine cortical bone by femtosecond laser ablation. The tests are performed in air, with a Yb:KYW chirped-pulse-regenerative amplification laser system (500 fs, 1030 nm) at fluences ranging from 0.55 to 2.24 J/cm2. The ablation process is monitored by acoustic emission measurements. The topography of the laser-treated surfaces is studied by scanning electron microscopy, and their constitution is characterized by glancing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 52 publications
1
31
1
Order By: Relevance
“…(5) and using the incubation coefficient value found in the present work (0.68 AE 0.08), single pulse ablation thresholds of 3.0 and 2.7 J∕cm 2 , respectively, were obtained, in good agreement with our result. The calculated value of the incubation coefficient 0.68 AE 0.08 is in good agreement with the value reported by Cangueiro et al 28 for bone. 31 This difference could be explained by the much shorter pulse duration and reduced wavelength of the laser used by Ji et al, 31 but Rode et al 29 found a single pulse ablation threshold of 2.2 J∕cm 2 using laser parameters similar to Ji et al (805-nm laser wavelength and 92-fs pulse duration).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…(5) and using the incubation coefficient value found in the present work (0.68 AE 0.08), single pulse ablation thresholds of 3.0 and 2.7 J∕cm 2 , respectively, were obtained, in good agreement with our result. The calculated value of the incubation coefficient 0.68 AE 0.08 is in good agreement with the value reported by Cangueiro et al 28 for bone. 31 This difference could be explained by the much shorter pulse duration and reduced wavelength of the laser used by Ji et al, 31 but Rode et al 29 found a single pulse ablation threshold of 2.2 J∕cm 2 using laser parameters similar to Ji et al (805-nm laser wavelength and 92-fs pulse duration).…”
Section: Discussionsupporting
confidence: 91%
“…The Raman spectra of the enamel specimens, normalized to the strongest peak, at 960 cm −1 , which corresponds to the ν 1 vibration of the phosphate group in hydroxyapatite, 28 are shown in Fig. 8.…”
Section: Raman Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fluence was calculated on the basis of the laser beam radius at e -2 of the maximum intensity of the Gaussian radiation intensity distribution, estimated using the D-squared method [20]. The laser beam was focused by a 100 mm focal length lens on a spot with a diameter of 338 ± 10 μm at e -2 at the surface of the specimen.…”
Section: Femtosecond Laser Treatmentmentioning
confidence: 99%